2019
DOI: 10.1002/cplu.201900262
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry, Stereodynamics, and Redox and Complexation Behaviors of 2,2′‐Diaryl‐1,1′‐Biazulenes

Abstract: 2,2′‐Diaryl‐1,1′‐biazulenes were synthesized and electronic communication between the azulene subunits was suggested based on redox measurements. The linkage of azulene at the 1‐position also appeared to increase the HOMO levels. In addition, cyclic voltammetry measurements of 2‐arylazulenes showed a return peak associated with the oxidation, which was not observed for azulene. The stabilization of the single‐electron oxidant may be due to the SOMO‐HOMO energy inversion phenomenon. X‐ray crystallography of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…In addition, a weak short-axis polarized L b band (ε = 308 M –1 cm –1 at 624 nm, 4aa ) was observed, which is derived from a S1 ← S0 transition. The latter displayed a clear vibrational fine structure and appeared in the range of 540 to 800 nm, similar to parent azulene and other azulene-fused π-conjugated systems. Moreover, due to their long-wavelength S1 ← S0 transition in the visible region, the compounds display blue or green colors, although the molar absorption coefficients ε are low.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, a weak short-axis polarized L b band (ε = 308 M –1 cm –1 at 624 nm, 4aa ) was observed, which is derived from a S1 ← S0 transition. The latter displayed a clear vibrational fine structure and appeared in the range of 540 to 800 nm, similar to parent azulene and other azulene-fused π-conjugated systems. Moreover, due to their long-wavelength S1 ← S0 transition in the visible region, the compounds display blue or green colors, although the molar absorption coefficients ε are low.…”
Section: Resultsmentioning
confidence: 96%
“…Azulene exhibits a non-mirror-symmetric frontier orbital geometry with a LUMO largely localized on the even positions and a HOMO with maximum density on the odd positions. This reduces the repulsive interaction between the two unpaired electrons and, thus, results in a small HOMO–LUMO energy gap. Azulene is known for its anomalous emission from S2, whereas the emission from S1 is negligible (an apparent violation of Kasha’s rule). This unique character of azulene can be explained by a low-lying S1 which endows a relatively large energy gap between S1 and S2, decreasing the rate of the S2 → S1 emission, and thus, the S2 → S0 fluorescence becomes dominant.…”
Section: Introductionmentioning
confidence: 99%
“…13). [32] Another example was reported by Casado, Nakamura, and their co-workers in 2021. [33] They observed that the radical trianion [S1] 3and the radical cation [As1] þ exhibited SHC.…”
Section: Other Radicalsmentioning
confidence: 85%
“…SHI in a dimer molecular design was also theoretically investigated in cationic azulene radical by Mazaki et al in 2019, 141 and more recently by Casado, Nakamura et al in 2021. 23 Interestingly, in the latter report, the authors explored spiro- conjugated systems with the ability to adopt SHI in both anionic and cationic radical forms (Fig.…”
Section: (I) Shi Radical With a Radical Fragment Weakly Interacting W...mentioning
confidence: 99%
“…Chemical structures of thiophene-based double helix radicals 16 and 17 •+ (TMS = trimethylsilyl). The molecular fragment in red highlights the predominant localization of the SOMO within the molecular structure.SHI in a dimer molecular design was also theoretically investigated in cationic azulene radical by Mazaki et al in 2019,141 and more recently by Casado, Nakamura et al in 2021 23. Interestingly, in the latter report, the authors explored…”
mentioning
confidence: 99%